ANALISIS EFEKTIVITAS KAHOOT SEBAGAI MEDIA PEMBELAJARAN BERBASIS GAME UNTUK MENINGKATKAN HASIL BELAJAR PPKN SISWA MIS YASIM ROKA - Julaiha; Edy Suparjan; Khairul Sani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The methods and media that are often used by teachers are generally lecture methods, which results in students quickly becoming bored with the learning process. This study was conducted to identify the effectiveness of kahoot in improving students PPKN learning outcomes. All 18 students from class 3 at MIS Yasim Roka were selected as subjects for the study. Data collection techniques using tests in the form of pre-test and post-test. The instrument in this study was to use a learning outcome test with 10 multiple choice questions and documentation as supporting data. The pre-test result showed that out of 18 students, only 1 student (5.56%) achieved the minimum completenedd score (score 65). In contrast, in the post-test, all 18 students (100%) managed to score above the Minimum Completion Criteria (KKM).